Frequency of Lentz Bodies Inclusion in Whole Blood Erythrocytes and Expanded Buffy Coat Smears - Camargo Castillo, Monica Alejandra; de Almeida, Bruno Albuquerque; Okano, Felipe Yuji; Menin, Angelica; Valle, Stella de Feira (Acta Scientiae Veterinariae, 2019)
Background: Canine distemper has been classified as highly contagious for most of domestic and wild carnivores, and the infection can be fatal. Canine distemper inclusion bodies, also denominated Lenz inclusion bodies, are large aggregates of viral nucleocapsid particles that can be form in red blood cells (RBCs), white blood cells (WBCs) and epithelial cells in many tissues during the acute phase of infection. Their presence in blood is transient and rarely encountered in light microscopy but are pathognomonic when identified in blood smears. The objective of this study was to investigate the frequency of distemper inclusions in erythrocytes according to the fraction of the sample used for blood smears. Materials, Methods & Results: The study was conducted with routine blood sample provided by the Veterinary Laboratory of Clinical Analysis from the Veterinary Teaching Hospital of Universidade Federal do Rio Grande do Sul. The EDTA-K2 blood sample of a 40 days old male dog, mixed breed, no immunization records, presenting diarrhea, hyporexia, myoclonus and pustules in the abdomen, was selected. In a routine peripheral blood smear examination, several distemper inclusions were observed in the erythrocytes. From this sample, ten smears were performed using a whole blood (WB) and top erythrocyte fraction combined with buffy coat, denominated of expanded buffy coat (EBC). The EBC fraction was obtained after centrifugation of EDTA whole blood in microhematocrit tubes at 9600 x g for 5 min to obtained the packed cell volume (PCV) and buffy coat. After centrifugation, the blood cells are separated into three layers based on density: platelets (adjacent to supernatant), WBCs, and RBCs in the bottom. The PCV was measured and the microhematocrit tube was ruptured 2% below the interface between leukocytes and plasma, deposited into a plastic microtubes, homogenized and used for blood smear preparation. All smears were stained with Diff-Quick Stain. The frequency of observation of RBCs with distemper inclusions bodies was performed under optical microscopy, in the immersion objective (100x), accounting for complete fields up to a minimum of 1000 RBCs, and compared between WB and EBC. In comparison between blood smears obtained from WB and EBC, a highly significant difference (P = 0.0004) was observed in the frequency distribution of distemper inclusion. The median of frequency of RBCs with distemper inclusions in a WB smears was 12.68/1000 RBCs (10.1 - 16.1/1000 RBCs), with a coefficient of variation (CV) of 12%. Median of frequency of distemper inclusions from EBC smears was 54.23/1000 RBCs (45-77.9/1000 RBCs), CV of 18% were observed. The median frequency of inclusions found in EBC smears was 4.27 times higher than the WB smears. Discussion: Buffy coat smear providing a concentrated preparation of nucleated cells and this procedure is useful to looking for low-incidence infectious organisms or other hematologic alterations. The upper fraction of the RBC column, below the buffy coat, is composed of young RBCs. Selection of these portion, and their possible formed in the bone marrow viral replication phase, could justified the increase in the frequency of RBCs containing viral inclusions in EBC, which would also increase the sensitivity of the technique. EBC was homogenized previously to make the smears, certifying the adequate cell distribution in the slide surface without interfere with the frequency of distemper inclusion in RBCs observation. These results were confirmed with the coefficients of variation. In conclusion, distemper inclusions bodies in RBCs from EBC is a recommended diagnosis method in patients suspected of canine Distemper infection. The observation being more frequent in the EBC in comparison with WB, commonly used in veterinary hematology.